The announcement effect of white collar crime on stock price by public listed companies in Malaysia - Tay, Liang Mui (Universiti Malaysia Sarawak (UNIMAS), 2014)
Since twentieth century, white collar crime has been present and become a widespread problem in the public. Nowadays, the growing of white collar crimes cases had pose much challenges toward enforcement agencies especially in developing countries such as Malaysia. Therefore, the share price event study is an important part of financial economics that can help researchers attempt to illustrate the impact of an event on firm’s stock returns. This study uses an event study methodology to examine the announcement effect of white collar crime towards the public listed firm on stock’s performance in Malaysia. The sample consists of 17 public announcements by 16 established public companies charged by Securities Commission for committing the white collar crime from the period of 1996 to 2013 in Malaysia. In this study, the daily basis of Average Abnormal Returns (AARs) and Cumulative Average Abnormal Returns (CAARs) with an event window of 90 days prior to and after the announcements has been determined. The finding indicates that an announcement of white collar crime has negative abnormal return on share price. As the result, the market does not reacting efficiently towards the information released regarding the incidence of white collar crime.